PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), CURRENT RATIO (CR) DAN DEBT TO EQUITY (DER) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2011 - Hilmi Abdullah; Eka Merdekawati (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, This research was conducted to examine the effect of variable Retun On Assets (ROA), Return on Equity (ROE), the Current Ratio (CR), and Debt to Equity Ratio (DER) on stock returns on companies listed in Indonesia Stock Exchange period 2009- 2011. The research population is 25 and the sample 19 companies. Data were obtained from the Indonesian Capital Market Directory (ICMD 2013) and analysis techniques used are multiple regression. The results obtained simultaneously adjusted R2 value of 0.027 means that 2.7% variation of stock returns can be explained by four independent variables are ROA, ROE, CR and DER, while the remaining 97.3% is explained by other variables not included in this research. The results showed no partial any of the variables that affect stock returns.